MARKETING REVIEW OF THE PHARMACEUTICAL MARKET ANTIHISTAMINE MEDICINES - I.A. Kostiuk; N.V. Sholoyko; V.A. Syatynia (Bogomolets National Medical University, 2016)
The article contains the results of the national pharmaceutical market's marketing analysis of antihistamine drugs. The researches in these pharmaceutical market field were carried out in such directions as: assortment of active ingredients and dosage forms, market structure of importing countries and domestic manufacturing companies of antihistamine drugs, usage during pregnancy and lactation., and usage in pediatric practice.